M(x)=2x^2+3 chứng tỏ M(x) không có nghiệm 19/08/2021 Bởi Emery M(x)=2x^2+3 chứng tỏ M(x) không có nghiệm
Đáp án: Giải thích các bước giải: $M(x)$ $=$ $2x^{2}$ $+$ $3$ $M(x)$ $=$ $2x^{2}$ $+$ $3$ $=$ 0 ⇔ $2x^{2}$ $=$ $-3$ Mà $2x^{2}$ ≥ $0$ ⇒ Đa thức vô nghiệm Bình luận
`\text{Đáp án:}` + `\text{Giải thích các bước giải:}` `\M(x)=2x^2+3` `M(x)=0``=> 2x²+3=0``=> 2x²=-3``=> x²=-3/2` `\text{(vô lí)}``\text{Vậy đa thức vô nghiệm}` Bình luận
Đáp án:
Giải thích các bước giải:
$M(x)$ $=$ $2x^{2}$ $+$ $3$
$M(x)$ $=$ $2x^{2}$ $+$ $3$ $=$ 0
⇔ $2x^{2}$ $=$ $-3$
Mà $2x^{2}$ ≥ $0$
⇒ Đa thức vô nghiệm
`\text{Đáp án:}` + `\text{Giải thích các bước giải:}`
`\M(x)=2x^2+3`
`M(x)=0`
`=> 2x²+3=0`
`=> 2x²=-3`
`=> x²=-3/2` `\text{(vô lí)}`
`\text{Vậy đa thức vô nghiệm}`